Monte carlo simulations of powder size reduction during mechanical milling process: An application to MgO - Thongon A. (2014)
In this study, the Monte Carlo Simulation was used to investigate the powder structure of magnesium oxide (MgO) undergoing the mechanical milling process as functions of milling time, initial temperature, milling frequency and amplitude of milling, in contacting with a heat bath. The Kawasaki algorithm was used to simulate the 'Ising powder' in a two-dimensional space. By allowing the shearing and diffusion effects, the competition between these two determines the sizes of the powders. The results show that the shearing effect reduces the particle sizes as the time goes while the diffusion effect enlarges the particle sizes. Furthermore, at fixed milling frequency and maximum amplitude of milling, both milling from adiabatic and heat exchange processes show that the maximum powder sizes are about the same at the beginning. However, at long milling time, the adiabatic and heat exchange processes provide smaller powder size as the system temperature is much larger that of the heat bath. Furthermore, the maximum size of powder takes longer time to form at the lower temperature, larger amplitude of milling, and longer milling time. As a result, this work suggests of how mechanical action and thermal effect play a crucial role on power size reduction at microscopic level. Copyright © Taylor &Francis Group, LLC.